2008
DOI: 10.1539/joh.k7002
|View full text |Cite
|
Sign up to set email alerts
|

Railways and Asbestos in Japan (1928–1987)—Epidemiology of Pleural Plaques, Malignancies and Pneumoconioses—

Abstract: consists of three parts. 1) Pleural plaques: Since the 1970s, pleural plaques have been regarded as evidence of past asbestos inhalation, and more recently recognized as a risk factor of asbestosrelated malignancies. For diagnostic criteria on plain radiographs, the modified ILO 1980 International Classification of Radiographs of Pneumoconioses was used. Most cases had pleural plaques with normal lungs. Large plant workers showed a significantly higher rate of plaques than workers in smaller plants. Bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…The CXR showed no lesions, while the chest CT scans demonstrated hyaline plaques in all 22 sites. These results are similar to those reported by Kishimoto et al 11) .…”
Section: Discussionsupporting
confidence: 93%
“…The CXR showed no lesions, while the chest CT scans demonstrated hyaline plaques in all 22 sites. These results are similar to those reported by Kishimoto et al 11) .…”
Section: Discussionsupporting
confidence: 93%
“…Unilateral pleural plaques were considered relevant only in the case of typical pleural features and, for the diagnosis of pulmonary asbestosis, a bilateral extent of the interstitial abnormalities was needed. This is in accordance with publications dealing with asbestos-related pleural abnormalities and with the weakness of the data about unilateral asbestosis [27,28]. After review, the same models were confirmed for pleural plaques, but were not significant for asbestosis due to an insufficient number of cases (data not shown).…”
Section: Occupational and Environmental Lung Disease C Paris Et Alsupporting
confidence: 89%
“…Numerous studies have examined the dose-or exposureresponse relation for pleural plaques (Bar-Shai et al, 2012;Boffetta, 1998;Clin et al, 2011;Eisenhawer et al, 2014;Ehrlich et al, 1992;Finkelstein & Vingilis, 1984;Hosoda et al, 2008;Jakobsson et al, 1995;Järvholm, 1992;Karjalainen et al, 1994;Lockey et al, 2015;Mastrangelo et al, 2009;McDonald et al, 1986;Moolgavkar et al, 2014;Paris et al, 2008Paris et al, , 2009Rohs et al, 2008;Sandén & Järvholm, 1986;Shepherd et al, 1997;Soulat et al, 1999;Van Cleemput et al, 2001). Results differ among these studies, 6 but exposure variables found relevant in one or more studies include time since first exposure (TSFE), age at first exposure (Jones, 1997), type (Hillerdal, 1997;Jones, 1997;Sandén & Järvholm, 1986) and dimensions of fiber (Hillerdal, 1997;Jones, 1997), lung fiber burden (Karjalainen et al, 1994;Roberts, 1971), duration of exposure, intensity of estimated asbestos exposure and cumulative exposure (measured in various ways).…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%